Mobile Blockchain in Digital Supply Chain - Riko Herwanto; Nisar Nisar; Chairani Fauzi; Fitria -; Amnah Amnah; Faurani I Santi Singagerda; Hary Sabita (Proceeding International Conference on Information Technology and Business, 2022)
Mobile device users are estimated to reach 4 billion in 2018 and 6 billions users in 2023. These mobile devices have changed how individuals and organizations carry out their activities. Increasing smartphone efficiency is changing how companies collaborate with their suppliers and distributors. Blockchain technology, which was first created for Bitcoin, is generating disruption in other industries. Even if the long-term forecasts for Bitcoin and the economy remain uncertain, it is increasingly evident that Blockchain technology can cause enormous disruption. However, because it poses a threat to the existing order of the modern world's prominent organizations, institutions, and power structures, its potential may never be fully realized. This article will introduce you to Blockchain technology and its potential use in the logistics and supply chain. If maintained on the Blockchain, data about supply chains and logistics can be sent across the network in a reliable, secure, and auditable manner. In some supply chain implementations, Blockchain is being replaced by distributed ledger technology, which offers several benefits. This article discusses the possible use of blockchain technology and mobile devices in the supply chain and logistics industryKeywords— Blockchain, Distributed Ledger, Mobile Device, Supply Chain, and Digital Supply Chain